Screening global set of barley germplasm for resistance to spot blotch disease in the warm-humid plains of Nepal - Pokharel, Bhanu Bhakta; Pandey, Madhav Prasad; Ghimire, Surya Kant; Thapa, Dhruba Bahadur; Manandhar, Hira Kaji; Rijal, Tirtha Raj; Thapa, Sailendra; Adhikari, Parbati; Verma, Ramesh Pal Singh; Gyawali, Sanjay (Journal of Cereal Research, 2021)
Spot blotch disease (SB) caused by Bipolaris sorokiniana (teleomorph: Cochliobolus sativus) is a major disease of barley and causes a significant yield loss under favorable conditions in the warm and humid areas. A global set of 340 barley germplasm obtained from ICARDA were evaluated for SB resistance under natural epiphytotic conditions along with two local checks (Bonus and Solu Uwa) at the research field of Nepal Agricultural Research Council, Rampur, Chitawan, Nepal for three consecutive years (2016-2018). Analysis of variance showed significant variation in Area Under Disease Progress Curve (AUDPC) of the studied genotypes in all the three years’ experiments. The check varieties were susceptible to SB (AUDPC value ≥ 750) in all the experiments. In the first-year experiment, 28, 105, 98 and 109 genotypes had resistant (R, AUDPC <250), moderately resistant (MR, AUDPC 250-499), moderately susceptible (MS, AUDPC 500-749), and susceptible (S, AUDPC≥750) type of disease reaction, respectively. In the second year, 1, 42, 136 and 161 genotypes showed R, MR, MS, and S type of disease reaction. In the third-year, 69 genotypes had MR, 132 MS and 139 S type of disease reaction. Summarized across the years, about 27 % genotypes had MS to MR or R type of SB reaction. The study identified barley lines that can be a potential source of SB resistance for barley breeding programs.